2018
DOI: 10.12968/bjon.2018.27.13.738
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self-reported side effects in neuroendocrine tumour patients prescribed somatostatin analogues

Abstract: Somatostatin analogues (SSA) are a common treatment for some forms of neuroendocrine tumours (NETs). Patients report a variety of side effects after starting these drugs, so in most cases they require a lot of nutritional input. The authors used an online survey to invite responses from patients worldwide to determine the extent of reported side effects. Patients were asked which SSA they were taking and how they rated the severity of their side effects. They were provided with a list of 11 options to choose f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Proportion of patients with GEP-NETs and diarrhoea due to various causes: Twenty-one articles on 18 unique studies reported quantitative data related to different causes of diarrhoea in patients with GEP-NETs (Table 1 )[ 6 , 23 - 41 ]. The majority of articles reported on PEI and associated steatorrhoea in patients receiving treatment with SSAs; 9.5% to 84% of patients with NETs in the included studies were reported to have experienced steatorrhoea[ 26 , 31 ], the primary symptom of PEI. In four articles in which the management of steatorrhea was reported, almost all patients with steatorrhoea were treated for PEI (96%-100%)[ 27 , 29 , 30 ]; however, only 62.5% of patients with steatorrhoea may have been treated in one study (14.3% of the overall study cohort) (Table 1 )[ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Proportion of patients with GEP-NETs and diarrhoea due to various causes: Twenty-one articles on 18 unique studies reported quantitative data related to different causes of diarrhoea in patients with GEP-NETs (Table 1 )[ 6 , 23 - 41 ]. The majority of articles reported on PEI and associated steatorrhoea in patients receiving treatment with SSAs; 9.5% to 84% of patients with NETs in the included studies were reported to have experienced steatorrhoea[ 26 , 31 ], the primary symptom of PEI. In four articles in which the management of steatorrhea was reported, almost all patients with steatorrhoea were treated for PEI (96%-100%)[ 27 , 29 , 30 ]; however, only 62.5% of patients with steatorrhoea may have been treated in one study (14.3% of the overall study cohort) (Table 1 )[ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…In four articles in which the management of steatorrhea was reported, almost all patients with steatorrhoea were treated for PEI (96%-100%)[ 27 , 29 , 30 ]; however, only 62.5% of patients with steatorrhoea may have been treated in one study (14.3% of the overall study cohort) (Table 1 )[ 40 ]. PEI was inferred from the reporting of steatorrhoea only in patients on SSAs in two publications, for example the presence of steatorrhoea “to varying degrees”[ 31 , 40 ]. It is important to acknowledge that this does not necessarily mean that these patients had PEI[ 31 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations